Barriers to Green Job Growth in Indonesia: Insights on Economic, Educational, and Social Challenges - Mas Davino Sayaza; Tjahjo Tri Hartono (Universitas Ibn Khaldun Bogor, 2024)
This study examines the barriers to green job development in Indonesia, focusing on economic, educational, and societal dimensions. Using a literature review methodology, the research synthesizes findings from academic studies, policy reports, and government publications to identify key challenges. Economic barriers include insufficient investment, inadequate fiscal incentives, and limited financial access for small and medium enterprises (SMEs). Educational barriers highlight a lack of targeted training programs, insufficient integration of sustainability in curricula, and disparities in access to education in rural areas. Societal barriers are reflected in low public awareness, negative perceptions of green jobs, and limited inclusion of marginalized communities. These challenges constrain the growth of green industries and limit workforce readiness for emerging sectors. The study concludes that addressing these barriers requires coordinated efforts, such as enhancing investments, reforming education systems, and fostering societal engagement.